2015
DOI: 10.1186/s12993-015-0072-x
|View full text |Cite
|
Sign up to set email alerts
|

DRD2 and DRD4 genes related to cognitive deficits in HIV-infected adults who abuse alcohol

Abstract: BackgroundHIV-infected individuals continue to experience neurocognitive deterioration despite virologically successful treatments. The causes of neurocognitive impairment are still unclear. However, several factors have been suggested including the role of genetics. There is evidence suggesting that neurocognitive impairment is heritable and individual differences in cognition are strongly driven by genetic variations. The contribution of genetic variants affecting the metabolism and activity of dopamine may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…We also acknowledge that a subset of the participants may have been experiencing current adversity, and a small number of individuals ( n  =   6) reported a history of mental health disorder, but these participants were not disproportionately distributed between genotype groups and it is therefore unlikely that these cases were driving the significant effects seen in our study. However, our sample comprised a male only population, predominately of Caucasian origin, which may have improved our ability to find variant effects specific to this population given mixed findings for general effects across gender and ethnicity for both COMT (Domschke, Deckert, O'Donovan, & Glatt, 2007; Gurvich & Rossell, 2015; Harrison & Tunbridge, 2008) and DRD2 (Gurvich & Rossell, 2015; Liu et al., 2014; Villalba et al., 2015). However, a recent study by Gurvich and Rossell (2015) failed to find an effect of COMT Val158Met genotype on cognition in males and it has been proposed that higher estrogen levels in females might amplify the effects of COMT , therefore affecting dopamine function differently from males (Colzato & Hommel, 2014; Gurvich & Rossell, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also acknowledge that a subset of the participants may have been experiencing current adversity, and a small number of individuals ( n  =   6) reported a history of mental health disorder, but these participants were not disproportionately distributed between genotype groups and it is therefore unlikely that these cases were driving the significant effects seen in our study. However, our sample comprised a male only population, predominately of Caucasian origin, which may have improved our ability to find variant effects specific to this population given mixed findings for general effects across gender and ethnicity for both COMT (Domschke, Deckert, O'Donovan, & Glatt, 2007; Gurvich & Rossell, 2015; Harrison & Tunbridge, 2008) and DRD2 (Gurvich & Rossell, 2015; Liu et al., 2014; Villalba et al., 2015). However, a recent study by Gurvich and Rossell (2015) failed to find an effect of COMT Val158Met genotype on cognition in males and it has been proposed that higher estrogen levels in females might amplify the effects of COMT , therefore affecting dopamine function differently from males (Colzato & Hommel, 2014; Gurvich & Rossell, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic studies looking at the association of DRD2 C957T with cognitive function have generally shown that CC homozygosity is associated with poorer performance on tests of executive function and working memory in the general population (Rodriguez‐Jimenez et al., 2006; Xu et al., 2007), decreased general cognitive ability in elderly healthy males and females (Bolton et al., 2010), impaired executive function and cognitive flexibility in HIV‐infected individuals who abuse alcohol (Villalba, Devieux, Rosenberg, & Cadet, 2015), and poorer performance in an attentional switching task in CC homozygotic females (Gurvich & Rossell, 2015). The T allele and TT homozygosity has been associated with better avoidance learning from negative outcomes in both forced choice and reaction time tasks (Frank, Doll, Oas‐Terpstra, & Moreno, 2009; Frank, Moustafa, Haughey, Curran, & Hutchison, 2007), better striatally mediated reflexive learning (Xie, Maddox, McGeary, & Chandrasekaran, 2015) and rule‐based category learning in healthy young adults (Byrne, Davis, & Worthy, 2016), and with superior performance in an attentional switching task in TT homozygotic males (Gurvich & Rossell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have looked at the effect of genetic polymorphisms related to the neurotransmitter dopamine, which is involved in executive function, working memory, and drugs-of-addiction and reward pathways in the CNS [ 60 , 64 ]. Dopamine is largely implicated in the fronto-striatal system, which consists of connections between the midbrain and prefrontal cortex, areas important for various cognitive functions.…”
Section: Genes Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…Those genotypes have been found to affect cognitive functioning in HIV-negative(−) populations, but their role in HAND is still unclear due to the limited number of reported studies [ 60 ]. Nonetheless, the genes encoding COMT and dopamine receptors do seem to be associated with various measures of NCIs in HAND populations [ 64 , 66 , 67 , 68 ]. Regarding the COMT gene locus (rs4680), it was found that the Met/Met genotype ( val158met ) was associated with improved performance in various executive functioning tests in HIV-infected individuals with mild cognitive impairment, but not in those concurrently using methamphetamine [ 66 ].…”
Section: Genes Involved In Neurotransmitter Systemsmentioning
confidence: 99%
“…A total of 267 HIV-infected alcohol abusers completed the study. Please refer to the study by Villalba et al [ 36 ] for participant characteristics. The Frascati criteria were used to measure neurocognitive impairment.…”
Section: Resultsmentioning
confidence: 99%